Self-love, egoism and the selfish hypothesis : key debates from eighteenth-century British moral philosophy - Maurer, Christian (Edinburgh University Press, 2019)
Do people only act out of self-interest? Or is there a less pessimistic explanation for human behaviour? Maurer delves into early-Enlightenment debates on self-love from both famous and lesser known A01s, including Lord Shaftesbury, Bernard Mandeville, Francis Hutcheson, Joseph Butler, Archibald Campbell, David Hume and Adam Smith.